Effects of starch gelatinization on weanling pig performance - Hongtrakul, K.; Bergstrom, J.R.; Nessmith, W.B., Jr.; Kim, I.H.; Goodband, Robert D.; Behnke, Keith C.; Nelssen, Jim L.; Tokach, Michael D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two hundred and ten weanling pigs were fed diets containing nonextruded corn (14.5% gelatinization; control) or corn that was extruded to provide 38.7%, 52.7%, 64.4%, or 89.3% starch gelatinization in the complete diet. With increasing gelatinization, ADG and ADFI decreased and then increased. but apparent digestibility of DM, CP, and energy increased then decreased. These results suggest that the degree of starch gelatinization has an inconsistent effect on weanling pig performance.
Keywords: Swine; Weanling pigs; Extrusion; Gelatinization